TOPOISOMERASE1α Acts through Two Distinct Mechanisms to Regulate Stele and Columella Stem Cell Maintenance . Issue 1 (11th March 2016) - Zhang, Yonghong; Zheng, Lanlan; Hong, Jing Han; Gong, Ximing; Zhou, Chun; Pérez-Pérez, José Manuel; Xu, Jian
Abstract : TOPOISOMERASE1α is required for survival of stele stem cells and maintenance of the undifferentiated state and number of columella stem cells in the Arabidopsis root. Abstract: TOPOISOMERASE1 (TOP1), which releases DNA torsional stress generated during replication through its DNA relaxation activity, plays vital roles in animal and plant development. In Arabidopsis ( Arabidopsis thaliana ), TOP1 is encoded by two paralogous genes ( TOP1α and TOP1β ), of which TOP1α displays specific developmental functions that are critical for the maintenance of shoot and floral stem cells. Here, we show that maintenance of two different populations of root stem cells is also dependent on TOP1α -specific developmental functions, which are exerted through two distinct novel mechanisms. In the proximal root meristem, the DNA relaxation activity of TOP1α is critical to ensure genome integrity and survival of stele stem cells (SSCs ). Loss of TOP1α function triggers DNA double-strand breaks in S-phase SSCs and results in their death, which can be partially reversed by the replenishment of SSCs mediated by ETHYLENE RESPONSE FACTOR115 . In the quiescent center and root cap meristem, TOP1α is epistatic to RETINOBLASTOMA-RELATED ( RBR ) in the maintenance of undifferentiated state and the number of columella stem cells (CSCs ). Loss of TOP1α function in either wild-type or RBR RNAi plants leads to differentiation of CSCs, whereas overexpression of TOP1α mimics and further enhances the effect of RBR reduction that increases the number of CSCs . Taken together, these findings provide important mechanistic insights into understanding stem cell maintenance in plants.